2021
DOI: 10.1134/s1070328421350013
|View full text |Cite
|
Sign up to set email alerts
|

Binuclear Complexes of Cu(II) and Mg(II) with 2-Furancarboxylic Acid: Synthesis, Structure, EPR Spectroscopy, and Results of In Vitro Biological Activity against Mycolicibacterium Smegmatis and SCOV3

Abstract: Using the reactions of copper(II) acetate magnesium(II) oxide with 2-furancarboxylic acid (HFur), compounds with chemical compositions [Cu 2 (Fur) 4 (MeCN) 2 ] (I) and [Mg 2 (Fur) According to the X-ray diffraction data (CIF files CCDC nos. 2085817 (I) and 2085818 (II)), both complexes have a binuclear structure. The metal core of I correspond to the tetracarboxylate bridged {Cu 2 (μ-Fur) 4 } complex, the coordination number of the copper atom in which is 5 (CuNO 4 ); in II, the metal atoms are linked by two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…6d). 24,40 This deactivation was observed by Huang et al where 2-furoic acid produced in situ through the Cannizzaro reaction blocked the active sites of the calcium catalyst by forming metal carboxylates. 41 Despite deactivation through the 2-furoic acid complex formation and carbonate deposition, the spent catalyst was successfully recycled for four runs via regeneration by calcination in air, as shown in Fig.…”
Section: Catalyst Leaching and Deactivationmentioning
confidence: 82%
“…6d). 24,40 This deactivation was observed by Huang et al where 2-furoic acid produced in situ through the Cannizzaro reaction blocked the active sites of the calcium catalyst by forming metal carboxylates. 41 Despite deactivation through the 2-furoic acid complex formation and carbonate deposition, the spent catalyst was successfully recycled for four runs via regeneration by calcination in air, as shown in Fig.…”
Section: Catalyst Leaching and Deactivationmentioning
confidence: 82%
“…4 belongs to a very widespread family of paddlewheel-type complexes: the [Cu 2 (carboxylate) 4 L 2 ] family. [46][47][48][49] Four HDISA units (Cu-O = 1.966 Å) connect two Cu atoms into a binuclear core (Cu⋯Cu = 2.668 Å). The -OH groups of HDISA are disordered over two positions with equal occupancies.…”
Section: [Cu(hdisa) 2 L 2 ]mentioning
confidence: 99%
“…13,26,30 The complexes of 3d-metals with 2-furoic acid (Hfur) studied previously showed bioactivity against mycobacterial strains, along with interesting magnetic and sorption properties. [32][33][34][35][36][37][38][39][40][41] In this work, we focused on the study of the self-assembly of 1-, 2-and 3-D coordination polymers by slow diffusion of a crosslinking ligand solution (1,2-bis(4-pyridyl)ethylene) into solutions of Ni II /Co II furoates in various solvents. Given the apparent simplicity of the suggested approach (no special conditions), it was observed that varying the solvents allowed polymers with various dimensions and structures to be formed.…”
Section: Introductionmentioning
confidence: 99%
“…13,26,30 The complexes of 3d-metals with 2-furoic acid (Hfur) studied previously showed bioactivity against mycobacterial strains, along with interesting magnetic and sorption properties. 32–41…”
Section: Introductionmentioning
confidence: 99%